Toward Water Security for Palestinians : West Bank and Gaza Water Supply, Sanitation, and Hygiene Poverty Diagnostic - World Bank Group (World Bank, Washington, DC, 2018)
The Palestinian territories face significant and growing shortfalls in the water supply available for domestic use. With population of approximately 4.8 million growing at an average annual rate of 2.8 percent, the domestic supply gap is projected to dramatically increase unless supply and service options are expanded. The Water Supply, Sanitation, and Hygiene Poverty Diagnostic (WASH PD) assesses the underlying causes of the chronic and growing water insecurity in the Palestinian territories to inform water and sanitation programming.